Understanding the Multidimensional Islamic Faith Through ‘Abd Al-Ghanī Al-Nābulusī’s Mystical Philosophy - Naoki Yamamoto (Al-Jami'ah: Journal of Islamic Studies, 2013)
This paper tries to present a new perspective on Islamic faith and Muslim identity to Muslim minorities who are challenged in practicing or following Islamic law in non-Islamic countries or non-Muslims in the contemporary world. It will uncover the multidimensional perspective of the concept of faith based on sin (dhanb) and repentance (tawbah) through the mystical philosophy of a Syrian scholar, Abd al-Ghanī al-Nābulusī (d. 1143/1741) of the 18th century Ottoman Damascus who contributed to the field of Sufism particularly based on Ibn ‘Arabī’s thought of waḥdat al-wujūd (oneness of being) and insān kāmil (the perfect man). Nābulusī believes that anyone who lived during the inexistence of prophet’s revelation, inhabited an isolated place cut off from information about Islam, or lived in dār al-ḥarb and did not make a hijra to dār al-islām could not be regarded as sinful in their deeds. However, faith in Allah is essential and infidelity is not forgiven regardless whether or not they live in dār al-islām or dār al-ḥarb. Further, Nābulusī insists that true faith can be achieved by understanding the sin of existence; the ignorance of the difference of existence between Allah and men.[Artikel ini menjelaskan identitas keberagamaan umat Islam minoritas yang dituntut untuk menerapkan syariat, namun harus hidup di negara non-muslim, dengan mendiskusikan perspektif multidimensional terhadap konsep dosa dan tobat khususnya konsep waḥdat al-wujūd dan insān kāmil yang dikembangkan oleh Abd al-Ghanī al-Nābulusī (1143/1741), seorang sufi pemikir Syria yang hidup di masa kesultanan Usmani di Damaskus. Nābulusī berkeyakinan bahwa siapa saja yang hidup sebelum turunnya wahyu di masa Nabi, hidup di daerah terpencil yang tidak mengenal Islam, atau hidup di dār al-ḥarb dan tidak hijrah ke dār al-islām, tidaklah dibebani dosa atas perbuatannya. Namun demikian, iman kepada Allah amatlah penting dan kekufuran tidaklah dimaafkan, baik seseorang tersebut hidup di dār al-islām ataupun dār al-ḥarb. Nābulusī beranggapan bahwa iman yang hakiki bisa dicapai dengan memahami dosa eksistensial, yaitu mempersamakan eksistensi Allah dan manusia.]